Secularism, Imam Hatip Schools, and the State’s Role in Shaping Islamic Education in Türkiye - Thoriquttyas, Titis; Nasih, Ahmad Munjin; Sulthoni, Achmad (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
Imam Hatip schools have historically employed a unique role within Türkiye’s education system, positioned at the intersection of religious instruction and secular governmental policy. Originally established to prepare religious leaders, these institutions have evolved into diverse entities that provide both religious and general education, heavily influenced by changing political ideologies and educational reforms. This study explores the historical development and current function of Imam Hatip schools, with a particular focus on how political dynamics and state interventions influence their institutional identity. Using a qualitative approach, the research combines semi-structured interviews, and document analysis. Primary data were collected from teachers, while secondary data included official documents, policy texts, and archival records. The case study of Imam Hatip Schools in Istanbul serves as the central focus, complemented by comparative references to other Imam Hatip schools. The findings suggest that the trajectory of these institutions is not solely determined by internal educational needs but is deeply intertwined with broader political narratives and the state's vision of Islamic education. This study concludes that Imam Hatip schools represent a contested and evolving space, where secularism, religious identity, and national policy continuously intersect. Their role in society remains dynamic, reflecting ongoing negotiations between tradition, modernity, and state control in Türkiye’s educational landscape.